Collision Glial Neoplasms Arising in an Ovarian Mature Cystic Teratoma: A Rare Event - Abdelrazak Meliti; Bayan Hafiz; Haneen Al-Maghrabi; Abdulrahim Gari (Case Reports in Pathology)
Germ cell neoplasms represent around 20% of all ovarian tumors. They most frequently affect children and young adults. Mature cystic teratoma is a common benign ovarian neoplasm comprising about 95% and is made up of all three germ cell embryonic layers. By definition, mature cystic teratoma may be derived from any of the three germ cell lines. On the other hand, immature teratomas contain primitive neuroepithelial elements. However, it is quite uncommon in the English literature to have a neuroepithelial glial neoplasm arising in a mature cystic teratoma of an adolescent. Interestingly enough, all published cases described a single type of glial neoplasm arising in mature ovarian teratoma. Herein, the authors discuss a unique case of concomitant occurrence of two different glial neoplasms, namely pilocytic astrocytoma and subependymoma arising in an ovarian mature cystic teratoma. To the best of our knowledge, this is the first reported case with such a distinctive histopathologic finding.